2014
DOI: 10.31018/jans.v6i2.436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variety and planting date of rice on population of natural enemies of brown planthopper, Nilaparvata lugens (Stal)

Abstract: Abstract. The present study on the effect of variety and planting date of rice on population of natural enemies of brown planthopper, Nilaparvata lugens (Stal) showed that during August, the mean population of spiders was statistically on par on CSR 30 and PR 114. The population differed with dates and was significantly (p=0.05) higher (9.0/10 hills)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The biotic agents like, predators and parasitoids are the natural regulators of insect pest population. Climate changes associated with alteration in sowing and planting dates have a profound effect on the insect pest incidences as well as the population of natural enemies [10] Rice is attacked by a number of pests, the stem borer being the major one, which cause losses up to 90 percent if not managed timely. Globally, stem borer alone causes yield losses of 10 million tones and accounts 50% of all insecticides used in the rice field.…”
Section: Introductionmentioning
confidence: 99%
“…The biotic agents like, predators and parasitoids are the natural regulators of insect pest population. Climate changes associated with alteration in sowing and planting dates have a profound effect on the insect pest incidences as well as the population of natural enemies [10] Rice is attacked by a number of pests, the stem borer being the major one, which cause losses up to 90 percent if not managed timely. Globally, stem borer alone causes yield losses of 10 million tones and accounts 50% of all insecticides used in the rice field.…”
Section: Introductionmentioning
confidence: 99%
“…However, Rajpoot et al (2019) concluded that the adjustment of rice planting late is the most practical way to inhibit rice stem borer (Scirpophaga incertulas Walker) infestation, as well as release of insect-resistant rice varieties. Tetarwal et al (2014) indicated that stem borers are globally controlled by insecticides, and about 50% of all insecticides applied in rice fields are directed to rice stem borer control. In general, both insecticides and biological control are difficult to adopt against rice stem borers because the insect larvae live mostly inside rice stems, and the adult activity in nocturnal.…”
Section: Discussionmentioning
confidence: 99%
“…However, Rajpoot et al (2019) concluded that the adjustment of rice planting late is the most practical way to inhibit rice stem borer (Scirpophaga incertulas Walker) infestation, as well as release of insect-resistant rice varieties. Tetarwal et al (2014) indicated that stem borers are globally controlled by insecticides, and about 50% of all insecticides applied in rice fields are directed to rice stem borer control. In general, both insecticides and biological control are difficult to adopt against rice stem borers because the insect larvae live mostly inside rice stems, and the adult activity in nocturnal.…”
Section: Discussionmentioning
confidence: 99%